Revisión genérica de Fulcidacini Jakobson, 1924 (Chrysomelidae, Cryptocephalinae) para México - Hernández-Sosa, Liliana; Romero-Nápoles, Jesús; Valdez-Carrasco, Jorge Manuel; Carrillo-Sánchez, José Luis; Ramírez-Alarcón, Samuel; Ordóñez-Reséndiz, María Magdalena; Niño-Maldonado, Santiago (Instituto de Ecología, A.C., 2019)
The fulcidacinos are phytophagous insects characterized by the presence of well-developed pronotal and elytral tubercles, which lead them to be confused with small clods or even excrement from other insects. Worldwide, the tribe Fulcidacini has 500 species, included in 11 genera. According to the species lists, were estimated that there are 54 to 74 species for Mexico, 76 species are recorded in this work. However, the taxonomic keys for identification of Mexican species are scarce; thus, with the purpose to contribute to the knowledge of the tribe in Mexico, taxonomic revision of the genera of Fulcidacini registered for the country is presented in this work. A dichotomous key is provided for identification and representative species are illustrated. Also included is a list of the Mexican species of each genus, with data on state distribution. Exema punctatipes is transferred to the genus Aulacochlamys due the carinae present in the pronotum; a particular feature of the genus.